RESPON PERTUMBUHAN, HASIL, DAN KUALITAS BEBERAPA VARIETAS SELADA KERITING (Lactuca sativa L.) TERHADAP APLIKASI PUPUK CANGKANG TELUR - Putri, Allisa Julia; Tobing, Oktavianus Lumban; Yuliawati, Yuliawati (JURNAL AGRONIDA, 2023)
Lettuce growth and production are influenced not only by cultivars but also by the environment and their interaction. Providing nutrition is part of cultivation techniques that can affect plant cultivars' growth, production and quality. Sources of plant nutrition can come from natural materials, one of which is eggshells. This research aimed to determine the effect of eggshell fertilizer on the growth, production and quality of several varieties of loose-leaf lettuce. The research was conducted from March to May 2022 in Gunung Putri, West Java. It was designed using a factorial, completely randomized design with three replications. Eggshell fertilizer consists of 5 levels, namely without eggshell fertilizer treatment, 50% recommendation (5 g per plant), 100% recommendation (10 g per plant), 150% recommendation (15 g per plant), and 200% recommendation (20 g per plant). Observed variables include growth, yield and quality characteristics. The Karina lettuce variety generally has superior growth and yield compared to the Kreibo variety but has relatively no differences from the New Grand Rapid variety. The Karina variety treated with eggshell fertilizer had a larger stem diameter than the one not treated with eggshell fertilizer. The Karina variety treated with eggshell fertilizer up to 200% has a higher dry weight and PTT content. The Karina variety, given the recommended 200% eggshell fertilizer, and the New Grand Rapid variety, given the recommended 100% eggshell fertilizer, produced the crispiest leaves. Eggshell fertilizer can potentially increase crop yields and quality, but further testing is needed to make it more optimal.